Toward Over 15% Power Conversion Efficiency for Organic Solar Cells: Current Status and Perspectives. Issue 12 (8th November 2017) - Zhang, Jianqi; Zhu, Lingyun; Wei, Zhixiang
Abstract: Significant improvement in the power conversion efficiency (PCE) of organic solar cells (OSCs) is achieved by developing novel donor and acceptor materials, optimizing the phase‐separation morphology via diversified strategies, and using interfacial materials for better charge‐carrier collection. For state‐of‐the‐art devices, a PCE of over 13% is reported. However, simulations indicate that an efficiency of ≈19% could be realized, assuming a total energy loss of 0.5 eV with an external quantum efficiency of 90% and a fill factor of 70%. This large difference between the theoretical calculations and the actual performance of the state‐of‐the‐art devices shows that OSCs have significant potential for the future. Here, the energy loss is discussed, which determines the PCE limit, and then different systems are reviewed, such as small‐molecule (SM)/fullerene blends, polymer/fullerene blends, SM/nonfullerene blends, polymer/nonfullerene blends, and multicomponent systems. After highlighting the factors that have limited the device efficiency to date, an outlook on the most important challenges to guide OSCs toward the 15% PCE regime is provided. Abstract : Minimizing the energy loss without reducing the fraction of charge carriers collected is crucial for optimizing the power conversion efficiency of a given material. Different organic‐solar‐cell systems are reviewed. After highlighting the factors that have limited the device efficiency to date, an outlook on the most important challenges to guide organic solar cells toward the 15% power conversion efficiency regime is provided.